Improving Students' Ability to Write Descriptive Text through Student Team Achievement Division (STAD) - Mantra, Ida Bagus Nyoman; Laton, Loisa (Journal on Studies in English Language Teaching (JOSELT), 2024)
The reality that has occurred so far is that many students struggle to write texts using English, which has encouraged teachers to conduct Classroom Action Research because student motivation is still low; this research aims to increase students' motivation and ability to learn English, incredibly Descriptive Text material. The image media used in this research are readily available around us, cheap, familiar, and attractive to students. The method used in this Classroom Action Research utilizes Student Team Achievement Division (STAD), which is project-based learning because it is also used to motivate students to write and even do good work. The subjects in the Classroom Action Research here are state middle school students. The research results show that image media dramatically increases students' motivation and ability to write Descriptive Text. Image media is exciting and effective as a source of ideas for students when generating ideas for writing descriptive text. So, in the end, students are motivated and able to write descriptive text well. Several things influence students' low motivation in writing recount text, including students finding English difficult, feeling bored with the learning situation, and students' lack of enthusiasm.